Idiopathic Membranous Nephropathy in Children in China. (1st June 2015) - Liu, An; Wu, Haibin; Su, Yufei; Wang, Lie; Xu, Guoshuang
<x xml:space="preserve">Abstract</x> Idiopathic membranous nephropathy (IMN), which was the result from non-SLE, non-hepatitis B or C virus infection, is relatively rare in children. We collected 584 pediatric cases of renal biopsy specimens in children hospitalized in Xijing Hospital from Jan 2008 to Dec 2013. We found that IgA nephropathy (27.9%) and Henoch-Schönlein purpura (26.4%) are the most common etiology of pediatric kidney disease, followed by minimal change disease (10.4%). Surprisingly, the prevalence of IMN is very high (7.5%) in pediatric patients. Moreover, the prevalence of IMN is quickly increasing from 4.4% in 2009 to 9.1% in 2013.